Analysis of the Determination of the Cost of Goods Sold at PT. Spirit Jaya Snack & Coffee - Mariana Rika Nahak; Elly Lestari; Fitria Setyaningrum (International Research & Development for Human Beings (IRDH), 2026)
The purpose of this study is to analyze the determination of the cost of goods sold at PT. Spirit Jaya Snack and Coffee. This research uses a qualitative method. The data used was an interview with the owner of PT. Spirit Jaya Snack and Coffee. The data analysis method used is descriptive with the cost of goods sold. The results of the analysis prove that the cost of goods sold in one production at PT. Spirit Jaya Snack and Coffee amounted to IDR 2,192,500 with the determination of the selling price of cassava chips per package of 100 grams at a price of IDR 13,000, with a profit of one production of IDR 1,707,500. The cost of goods sold plays an important role in determining the amount of expenses and expenses incurred to produce items or services of a business entity, as well as to determine the accurate selling price of the product.